Expanded Indications for Tricuspid Valve Regurgitation Repair - Manenti, Antonio; Pagnoni, Gianluca; Vicenzi, Aurora; Coppi, Francsca (The Thoracic and Cardiovascular Surgeon)
Not Available, as a letter to the editor.